Electrophysiological monitoring of the nonrecurrent inferior laryngeal nerve and radiological evaluation of concurrent vascular anomalies - Sormaz, Ismail Cem; Iscan, Ahmet Yalin; Tunca, Fatih; Kostek, Mehmet; Aygun, Nurcihan; Matlim Ozel, Tugba; Soytas, Yigit; Poyanli, Arzu; Sari, Serkan; Uludag, Mehmet; Giles Senyurek, Yasemin (Frontiers in Endocrinology, 2024)
Purpose: The objective of this study was to characterize the electrophysiological characteristics of nonrecurrent inferior laryngeal nerves (NRILNs) that were dissected via intraoperative neuromonitoring (IONM) and concomitant vascular anomalies in patients with NRILNs. Methods: A retrospective analysis was conducted on 7865 patients who underwent thyroidectomy with IONM at three tertiary referral centers. The study included 42 patients in whom an NRILN was detected. IONM data and postoperative vocal cord (VC) examinations were recorded for all patients. The absence of an initial vagal EMG response and/or a short (<3.5 ms) latency period during the initial vagal stimulation or the inability to identify the RLN within the Beahrs triangle was considered highly suspicious for the presence of an NRILN. Postoperative cross-sectional imaging was performed in 36 out of 42 patients to assess any concurrent vascular anomalies.Results: The prevalence of NRILN was 0.53%. An NRILN was suspected due to EMG findings in 32 (76%) patients and the inability to identify the RLN within the Beahrs triangle in the remaining 10 (24%) patients. The mean right VN latency period was 3.05 ± 0.15 ms. The V1 latency period of the right VN was shorter than 3.5 ms in 39 (93%) and longer than 3.5 ms in 3 (7%) patients. One of these three patients with latency>3.5ms had a large mediastinal goiter. Transient VC paralysis occurred in one (2.4%) patient. Of the 36 patients with postoperative imaging data, 33 (91.4%) had vascular anomalies. All 33 patients had aberrant right subclavian arteries, and 13 (39.4%) also had accompanying additional vascular anomalies.Conclusions: The NRILN is an anatomical variation that increases the risk of nerve injury. Observation of an absent EMG response and/or a short latency period during the initial vagal stimulation facilitates the detection of an NRILN at an early stage of thyroidectomy in the majority of patients.